Critical analysis skills for social workers - Wilkins, David; Boahen, Godfred (Maidenhead : Open University Press, 2013)
Analysis is a critical skill for social workers, yet it is a skill that many practitioners find very difficult. This book will help social workers to improve their analysis skills by offering a very basic, step-by-step model to develop an analytical mindset. It shows how analysis can be woven into the whole process of social work engagement, resulting in better decision making, more efficient ways of working and, ultimately, better outcomes for social work service users. -- Publisher website.
Introduction -- Critical analysis : what, how and why? -- Skills for critical analysis -- Emotion and intuition -- Approaches to analysis -- Toosl for critical analysis -- Guided case examples -- Supervision, reflection and critical analysis -- Conclusion -- Appendices -- Notes -- References -- Index.
Includes bibliographical references : (p. [135]-141) and index.
Keywords: Social service; Social workers